Godzilla : here there be aliens - Tieri, Frank (Godzilla: Here There Be Aliens, 2026)
"It's total carnage on Earth as the Xiliens invade with the help of kaiju from outer space in this exciting graphic novel! It's the middle of the 20th century, and Americans everywhere are terrified of the strange lights hovering above them in the night sky...and they should be. These UFOs are actually the Xilien invasion force! Revealed to have already been on Earth during the events of Here There Be Dragons: Sons of Giants, the Xiliens have been attempting to destabilize the planet with the help of kaiju from outer space. With the aliens' claws deep inside the U.S. government, will our rogue operatives manage to band together to save humanity?"--Amazon.com.